2004
DOI: 10.1136/gut.2002.009936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antiviral treatment on evolution of liver steatosis in patients with chronic hepatitis C: indirect evidence of a role of hepatitis C virus genotype 3 in steatosis

Abstract: Background and aim: Recent studies suggest that liver steatosis in chronic hepatitis C may be the expression of a direct cytopathic effect of hepatitis C virus (HCV), particularly in patients infected with genotype 3. To investigate this hypothesis, we studied the relationship between steatosis evolution and HCV clearance after antiviral treatment in patients with chronic hepatitis C and paired liver biopsies. Methods: A total of 151 patients (37 with HCV genotype 3; 114 with HCV non-3 genotypes) were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 27 publications
11
81
1
5
Order By: Relevance
“…This possibility would also explain why steatosis is often associated with fibrosis in cross-sectional studies and might correlate with progression of fibrosis in longitudinal studies when initial disease severity was not controlled for adequately. [16][17][18][19][20]29 Thus, these findings might indicate that steatosis is the result rather than the cause of disease severity and disease progression.…”
Section: Discussionmentioning
confidence: 92%
“…This possibility would also explain why steatosis is often associated with fibrosis in cross-sectional studies and might correlate with progression of fibrosis in longitudinal studies when initial disease severity was not controlled for adequately. [16][17][18][19][20]29 Thus, these findings might indicate that steatosis is the result rather than the cause of disease severity and disease progression.…”
Section: Discussionmentioning
confidence: 92%
“…In a series of patients with genotype 3 and steatosis, a sustained virological response led to regression of steatosis in 91% of the cases, a much higher index than the 19% observed for those who did not present sustained virological response [6], making the cytopathic effect a more consistent cause of steatosis. Other authors have reported similar results [22,36].…”
Section: Steatosismentioning
confidence: 99%
“…The evaluation of the presence of steatosis, its scoring, and the evaluation of the presence of associated steatohepatitis has gradually become more important [6,7,12,16,19,20,24,[29][30][31][32]36,40].…”
Section: Steatosismentioning
confidence: 99%
“…Several reports have demonstrated a statistically significant relationship between HCV genotype 3, the injecting drug abuse, and a younger age of infection [45][46][47][48][49]. Moreover, by comparing patients infected with genotype 3 and those infected with other genotypes, numerous groups have revealed an association between this genotype and hepatic steatosis [50][51][52][53][54][55], and a severe histopathological manifestation of CHC which can improve after achieving SVR with the antiviral treatment [56][57][58].…”
Section: Molecular Epidemiology Of Hcv Genetic Diversity and Its Clinmentioning
confidence: 99%